Analysis of Acceleration Signals using Wavelet Transform - Sekine, M.; Tamura, T.; Akay, M.; Togawa, T.; Fukui, Y. (Methods of Information in Medicine, 2000)
In this study, we attempted to discriminate the acceleration signal for horizontal level and stairway walking using wavelet-based fractal analysis method. The acceleration signal was measured close to the center of gravity of the body, while the subjects walked continuously in the corridor and up and down the stairs. We used the wavelet-based fractal analysis method to discriminate walking pattern. The parameter H which is related directly to the fractal dimension was estimated by the wavelet coefficient and was changed into low value during walking upstairs. By manually setting the threshold level for individual, it was possible to discriminate walking upstairs from the other walking type. However, the common feature among subjects was not shown between level walking and walking downstairs.
Keywords: Gait; Acceleration; Wavelet Transform; Fractal Dimension